Integration of Islamic Jurisprudence Principles within the UN Global Human Security Framework - Munawar Fuad (UIN Sunan Gunung Djati, 2024)
This study explores the integration of Islamic jurisprudence principles, particularly maqÄá¹£id al-SharÄ«Ê¿a (objectives of Islamic law) and á¸awÄbiá¹ (regulatory principles ensuring adherence to justice and moderation), into the United Nations' (UN) Global Human Security Framework. Using a recommendatory legal research methodology, this study analyses international legal documents, such as UNGA Resolution 66/290, and classical Islamic texts, including Al-Ghazaliâ€™s Al-Mustasfa. The findings reveal a strong alignment between maqÄá¹£id al-SharÄ«Ê¿a and the human security dimensions outlined by the UN, encompassing protection of religion, life, intellect, lineage, and wealth. By incorporating Islamic principles, this research offers a culturally inclusive and ethically grounded approach to global security challenges. The application of á¸awÄbiá¹ highlights the importance of balancing justice and moderation in addressing critical issues such as economic inequality, humanitarian crises, and governance challenges. This study contributes to the discourse on global human security by proposing a novel framework that bridges religious law and international governance, providing a foundation for future interdisciplinary studies.